Economic Analysis of Supply Functions, Private Returns to Investment in Education and Skill Mismatch in Egypt - Marwa Shibl Biltagy (European Journal of Government and Economics (EJGE), 2019)
Education provides good health, empowerment and employment to all people in the society. Accordingly, education can make a lifelong difference in individuals' lives. It is proved that, on average, there is a positive relationship between each additional year of schooling and the income of an individual. The main objective of this paper is to estimate the demand and supply functions for schooling in Egypt using the data of the Egypt Labor Market Panel Survey 2012. It is estimated that the private rate of return to education is 4.5%. Moreover, the rate of return to the number of years of experience is 2.6%, i.e. each additional year of experience will increase the earnings of an individual by 2.6% on average. It is concluded that individuals from poor families have an increased likelihood of receiving financial aid, which decreases their discounting rate of interest.
Keywords: I21; I26; 330; investments in education; supply functions for schooling; skill mismatch